Recent progress on metamaterials: From effective medium model to real-time information processing system. (September 2019) - Fu, Xiaojian; Cui, Tie Jun
Abstract: Electromagnetic (EM) metamaterials are artificially engineered media composed of subwavelength unit cells, which achieve exotic EM properties beyond the limits of natural materials and provide great freedom to manipulate EM waves. Here, we review the recent progress on metamaterials in terms of three aspects: effective medium metamaterials, plasmonic metamaterials, and information metamaterials, respectively. In the first section for the effective medium metamaterials, we summarize the fundamental physics and typical applications such as invisibility cloaks, lenses, antennas, and other passive devices. Tunable, reconfigurable, and active metamaterials are also introduced. In the second section, we review the research progress of single plasmons at optical frequencies, and then present highly efficient excitation methods of spoof surface plasmon polaritons (SPPs) and introduce typical passive and active SPP devices such as waveguides, beam splitters, filters, directional couplers, amplifiers, and second harmonic generators. SPP on-chip components and circuits are also investigated with the remarkable advantages in crosstalk reduction to solve the signal-integrity problem, which has challenged to the microwave devices and integrated circuit technologies for many years. Subsequently, spoof localized surface plasmons (LSPs) having novel resonant modes and potential application in high sensitivity sensors are illustrated. In the third section, we first give a brief introduction of EM metasurfaces as well as their applications in generation of optical vortex beams, holograms, and metalenses, and then give a comprehensive review on the recently proposed information metamaterials, including digital coding metamaterials and field-programmable metamaterials, by taking account of the physical principles and their new functions in real-time manipulation of the EM waves such as anomalous reflections or refractions, radar cross section (RCS) reductions, and beam scanning. We further demonstrate the applications of programmable metamaterials in programmable radar, imaging, wireless communication, and hologram systems. Finally, an outlook of the future directions of metamaterials is offered.